Vaginal assessment and expedited amniotomy in oral misoprostol labor induction in nulliparas: a randomized trial - Win, Sandar Tin; Tan, Peng Chiong; Balchin, Imelda; Khong, Su Yen; Si, Lay Khaing; Omar, Siti Zawiah (Elsevier, 2019)
Background: Labor is induced in 20−30% of maternities, with an increasing trend of use. Labor induction with oral misoprostol is associated with reduced risk of cesarean deliveries and has a safety and effectiveness profile comparable to those of mechanical methods such as Foley catheter use. Labor induction in nulliparous women continues to be challenging, with the process often quite protracted. The eventual cesarean delivery rate is high, particularly when the cervix is unfavorable and ripening is required. Vaginal examination can cause discomfort and emotional distress particularly to nulliparous women, and plausibly can affect patient satisfaction with the induction and birth process. Objective: The aim of this study was to evaluate regular (4-hourly prior to each oral misoprostol dose with amniotomy when feasible) compared with restricted (only if indicated) vaginal assessments during labor induction with oral misoprostol in term nulliparous women Materials and Methods: We performed a randomized trial between November 2016 and September 2017 in a university hospital in Malaysia. Our oral misoprostol labor induction regimen comprised 50 μg of misoprostol administered 4 hourly for up to 3 doses in the first 24 hours. Participants assigned to regular assessment had vaginal examinations before each 4-hourly misoprostol dose with a view to amniotomy as soon as it was feasible. Participants in the restricted arm had vaginal examinations only if indicated. Primary outcomes were patient satisfaction with the birth process (using an 11-point visual numerical rating scale), induction to vaginal delivery interval, and vaginal delivery rate at 24 hours. Results: Data from 204 participants (101 regular, 103 restricted) were analyzed. The patient satisfaction score with the birth process was as follows (median [interquartile range]): 7 [6−9] vs 8 [6−10], P = .15. The interval of induction to vaginal delivery (mean ± standard deviation) was 24.3 ± 12.8 vs 31.1 ± 15.0 hours (P = .013). The vaginal delivery rate at 24 hours was 27.7% vs 20.4%; (relative risk [RR], 1.4; 95% confidence interval [CI], 0.8−2.3; P = .14) for the regular vs restricted arms, respectively. The cesarean delivery rate was 50% vs 43% (RR, 1.1; 95% CI, 0.9−1.5; P = .36). When assessed after delivery, participants’ fidelity to their assigned vaginal examination schedule in a future labor induction was 45% vs 88% (RR, 0.5; 95% CI, 0.4−0.7; P < .001), and they would recommend their assigned schedule to a friend (47% vs 87%; RR, 0.6; 95% CI, 0.5−0.7; P < .001) in the regular compared with the restricted arms, respectively. Conclusion: Despite a shorter induction to vaginal delivery interval with regular vaginal examination and a similar vaginal delivery rate at 24 hours and birth process satisfaction score, women expressed a higher preference for the restricted examination schedule and were more likely to recommend such a schedule to a friend. © 2019 Elsevier Inc.